THE ROLE OF WEST JAVA OMBUDSMAN REPRESENTATIVE IN SUPERVISING PUBLIC SERVICE AS VIEWED FROM SIYASAH DUSTURIYAH - Mutiara Jihan Aziza; Chaerul Shaleh; Taufiq Alamsyah (Jurnal Ilmiah Advokasi, 2025)
Supervision of public services by the West Java Representative Ombudsman plays an important role in ensuring the quality of service and the protection of public rights. However, the implementation is still facing obstacles. This has an impact on the low effectiveness of supervision. In the perspective of Siyasah Dusturiyah, supervision must uphold the principles of justice, transparency, and accountability according to sharia values. This research aims to analyze the stages of supervision by the Ombudsman, identify the obstacles faced, and review its implementation based on the principle of Siyasah Dusturiyah. The research method uses an empirical juridical approach with descriptive-qualitative. Data is collected through interviews, document studies and observations. Based on research, the obstacles experienced by the West Java Representative Ombudsman are caused by several factors. First, the limitation of human resources. The West Java Representative Ombudsman has only 15 members to supervise 22 regencies/cities. Furthermore, the low level of public participation, one of which is due to the unfamiliarity of the Ombudsman's name as a supervisory institution among the community.Keywords: Function, Service, Supervision, Siyasah Dusturiyah